Uso dos eliciadores acibenzolar-s-metílico e harpina na indução de resistência em plantas de feijoeiro comum ao crestamento bacteriano - Bressan, Dayanne Fabrício (2011)
The common bacterial blight, caused by Xanthomonas axonopodis pv. phaseoli is one of the major diseases of the bean crops. In search for alternatives to control the plant diseases, the use of the elicitors / inductors of resistance has been explored. Thus, the objective of this work was to verify the effectiveness of the elicitors harpina and acibenzolar-S-methyl in the induction of the defense mechanisms in bean plants (Phaseolus vulgaris L.) against common bacterial blight caused by X. axonopodis pv. phaseoli, evaluating the possible changes in the process of gas exchange and the activation of the key enzymes involved in the plant defense - peroxidase, superoxide dismutase, besides proteins and phenols. It was used seeds from IAPAR 31 and IPR Colibri cultivars. After emerged the first trifoliate leaves in the vegetative stage (V3) the plants were treated with the elicitors Acibenzolar-S-methyl and harpina, and distilled water (control). Seven days after the first application of the elicitors, the pathogen was inoculated on the leaves of bean plants. The severity assessment was performed every 10 days and the first evaluation 15 days after the pathogen inoculation. The measurement photosynthesis were performed 40 days after the inoculation when the symptoms and the damages of the disease showed themselves established. To carry out the biochemical analysis, samples of leaf tissue from each treatment were collected 24 hours before, 24, 48 and 72 hours after the application of the elicitors. Also, it was determined the yield and its components in both cultivars. The application of ASM and harpina provided the reduction in the severity of the common bacterial blight disease of the bean plants of IPR-Colibri cultivars and the same trend was observed for the IAPAR 31 cultivars treated with the elicitor ASM. Plants by IAPAR 31 treated with the elicitor ASM showed higher rates of assimilation of CO2 when compared to the control and the same trend was observed for cultivar IPR-Colibri. The application of ASM promoted the increase of the antioxidative enzyme peroxidase activity, and the induction of the phenolic compounds synthesis and, especially in the susceptible cultivar IPR-Colibri. For grain yield and its components, significant differences were not observed between the control and the elicitors ASM and harpina. The elicitors ASM and harpina induced the resistance mechanisms in bean plant against X. axonopodis pv. phaseoli, indicating the potentiality of the elicitor utilization in bean crops.